Malaria and land use: A spatial and temporal risk analysis inn southern Sri Lanka - Klinkenberg, E.; Van der Hoek, W.; Amerasinghe, F.P.; Jayasinghe, G.; Mutuwatte, L.; Guanawardena, D.M. (Colombo (Sri Lanka), 2003)
Sumario (En)
Ilus., 60 ref.
Keywords: MALARIA; USO DEL AGUA; UTILIZACION DE LA TIERRA; POLUCION DEL AGUA; ENTORNO SOCIOECONOMICO; ESTUDIOS DE CASOS PRACTICOS; DISTRIBUCION GEOGRAFICA; SALUD PUBLICA; CONTROL DE ENFERMEDADES; SRI LANKA